Community Stucture of Epiphytic Diatoms on Seagrass Leaves of Enhalus acoroides in Jago-Jago Coastal Waters of Tapanuli Tengah North Sumatera Province - Bornok Silalahi; Sofyan Husein Siregar; Zulkifli ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted in March 2015 in the coastal waters of the village of Jago-Jago Central Tapanuli, North Sumatra. The aim of this research was to know the community structure of epiphytic diatom which include the type and abundance, diversity, uniformity and epiphytic diatom dominance contained in the leaves of Enhalus acoroides and to know the characteristics of the diatom habitat includes water quality parameters that affect the existence of epiphytic diatoms. Data were obtained by direct observation, measurement and sampling in the field followed by the identification of the type (species) of epiphytic diatom at the Marine Biological Laboratory, University of Riau. The results showed Total epiphytic diatoms found were 30 genera. The highest abundance of diatoms were Nitzschia and Skeletonoma that were recorded in station III. This genus has high adaptability pitch on the environment so that it can grow and develop properly. Diatom abundance of epiphytes on the leave base, middle and tip of the station I ranged from 31.093 to 71.035 ind/cm2, in the station II ranged from 59.093 to 92.855 ind/cm2 and at stations III ranged from 33.562 to 82.460 ind/cm2. The highest abundance of epiphytic diatoms was found in station II, ie 75.013 ind/cm2, while the lowest abundance was found in station I, 48.935 ind/cm2. The value of diversity index (H '), dominance index (D) and uniformity index (E), concluded that quality was diversity of species were, no species dominated and water quality was still in favorable condition to support the life of epiphytic diatoms.Key Words: Community Structure, Epiphytic Diatoms, Enhalus acoroides, TapanuliTengah